Antiglioma activity of GoPI-sugar, a novel gold(I)-phosphole inhibitor: Chemical synthesis, mechanistic studies, and effectiveness in vivo - Jortzik, Esther; Ahmadi, Rezvan; Helmke, Burkhard Maria; Unterberg, Andreas; Herold-Mende, Christel (Biochimica et biophysica acta. Proteins and proteomics, 2014)
Glioblastoma, an aggressive brain tumor, has a poor prognosis and a high risk of recurrence. An improved chemotherapeutic approach is required to complement radiation therapy. Gold(I) complexes bearing phosphole ligands are promising agents in the treatment of cancer and disturb the redox balance and proliferation of cancer cells by inhibiting disulfide reductases. Here, we report on the antitumor properties of the gold(I) complex 1-phenyl-bis(2-pyridyl)phosphole gold chloride thio-β-d-glucose tetraacetate (GoPI-sugar), which exhibits antiproliferative effects on human (NCH82, NCH89) and rat (C6) glioma cell lines. Compared to carmustine (BCNU), an established nitrosourea compound for the treatment of glioblastomas that inhibits the proliferation of these glioma cell lines with an IC50 of 430μM, GoPI-sugar is more effective by two orders of magnitude. Moreover, GoPI-sugar inhibits malignant glioma growth in vivo in a C6 glioma rat model and significantly reduces tumor volume while being well tolerated. Both the gold(I) chloro- and thiosugar-substituted phospholes interact with DNA albeit more weakly for the latter. Furthermore, GoPI-sugar irreversibly and potently inhibits thioredoxin reductase (IC50 4.3nM) and human glutathione reductase (IC50 88.5nM). However, treatment with GoPI-sugar did not significantly alter redox parameters in the brain tissue of treated animals. This might be due to compensatory upregulation of redox-related enzymes but might also indicate that the antiproliferative effects of GoPI-sugar in vivo are rather based on DNA interaction and inhibition of topoisomerase I than on the disturbance of redox equilibrium. Since GoPI-sugar is highly effective against glioblastomas and well tolerated, it represents a most promising lead for drug development. This article is part of a Special Issue entitled: Thiol-Based Redox Processes.